Application of chemometric approach for development and validation of high performance liquid chromatography method for estimation of ropinirole hydrochloride. Issue 21 (30th September 2019) - Fatima, Saman; Beg, Sarwar; Samim, Mohammed; Ahmad, Farhan J.
Abstract: A systematic Quality by Design approach was employed for developing an isocratic reversed‐phase liquid chromatographic technique for the estimation of ropinirole hydrochloride in bulk drug and pharmaceutical formulations. LiChrospher RP 18‐5 Endcapped column (25 cm × 4.6 mm id) at ambient temperature (25 ± 2°C) was used for the chromatographic separation of the drug. The screening of factors influencing chromatographic separation of the active pharmaceutical ingredient was performed employing fractional factorial design to identify the influential factors. Optimization of the selected factors was carried out using central composite design for selecting the optimum chomatographic conditions. The mobile phase employed was constituted of Solvent A/Solvent B (65:35 v/v) (Solvent A [methanol/0.05 M ammonium acetate buffer, pH 7, 80:20 v/v] and Solvent B [high performance liquid chromatography grade water]) and used at 0.6 mL/min flow rate, while UV detection was performed at 250 nm. Linearity was achieved in the drug concentration range 5–100 µg/mL ( R 2 = 0.9998) with limits of detection and quantification of 1.02 and 3.09 µg/mL, respectively. Method validation was performed as per ICH guidelines followed by forced degradation studies, which indicated good specificity of the developed method for detecting ropinirole hydrochloride and its possible degradation products in the bulk drug and pharmaceutical formulations.